2008
DOI: 10.1177/0095798408323384
|View full text |Cite
|
Sign up to set email alerts
|

Black Canadians' Coping Responses to Racial Discrimination

Abstract: On the basis of a cultural coping framework, the present study examined coping responses to racial discrimination among 190 Black Canadians. The study assessed the respondents' coping with both general (i.e., problem-and emotionfocused coping) and Africultural coping strategies (i.e., spiritual-centered, collective, and ritual-centered coping) across three different racial discrimination vignettes (i.e., interpersonal, institutional, and cultural discrimination). Furthermore, three individual and cultural diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 45 publications
0
48
0
Order By: Relevance
“…Indeed, prior research that has examined race-related stress as a multidimensional construct has found that cultural racial discrimination contributes the greatest proportion of variance to adverse mental health outcomes (Carter & Reynolds, 2011), and that individuals are more likely to perceive discrimination as directed toward one's ethnocultural group than to themselves (Taylor et al, 1990). Joseph and Kuo (2009) observed that African Americans were most likely to endorse problem solving, cognitive/emotional debriefing, and collective coping as responses to cultural discrimination. Stigmatization due to cultural discrimination is less likely due to the actions of a specific perpetrator, and thus less amenable to direct coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prior research that has examined race-related stress as a multidimensional construct has found that cultural racial discrimination contributes the greatest proportion of variance to adverse mental health outcomes (Carter & Reynolds, 2011), and that individuals are more likely to perceive discrimination as directed toward one's ethnocultural group than to themselves (Taylor et al, 1990). Joseph and Kuo (2009) observed that African Americans were most likely to endorse problem solving, cognitive/emotional debriefing, and collective coping as responses to cultural discrimination. Stigmatization due to cultural discrimination is less likely due to the actions of a specific perpetrator, and thus less amenable to direct coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In such a situation, making a plan or filing a formal complaint may be seen as impractical because the perpetrator is a stranger, has little responsibility to the victim, and is unlikely to be encountered again. Interpersonal forms of racial discrimination may yield fewer opportunities for more contemplative forms of coping responses such as planful problem solving coping and instead pull for more immediate coping responses (Joseph & Kuo, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In a Canadian study, Joseph and Kuo (2009) examined Black Canadians’ coping responses with three racial discrimination situations (interpersonal, cultural, and institutional). The study found that Black Canadians adopted a mixture of both Africultural and conventional coping strategies (e.g., problem‐ and emotion‐focused coping) in dealing with discrimination in a context‐dependent fashion.…”
Section: Empirical Research Evidence For Collective Copingmentioning
confidence: 99%
“…As a whole, the advent of these measures represents a significant step forward to counterbalance the individualistic and “acontextual” biases in the conventional measurement approach used to assess coping. While this development is highly encouraging, a review of the literature also showed that only four studies were published in the past five years (Horn, 2008; Joseph & Kuo, 2009; Kim, 2009; Wei et al., 2010) based on any of these six cultural coping measures. Clearly, more extensive research to discern the validity, the utility, and the generalizability of these coping measures is needed.…”
Section: Measurements Of Collective Copingmentioning
confidence: 99%
See 1 more Smart Citation